THE IMPACT OF OFFSHORE MANUFACTURING ON QUALITY PERCEPTIONS - Mark W. Speece ,; Yukiko Kawahara ,; Chip E. Miller, (Asian Academy of Management Journal, 1996)
As competition in world markets intensifies, moving production offshore has been one key strategy of many firms in industrial countries, including those in Japan and the USA Some offshore manufacturing is undertaken to ensure market access, as is often the case when firms from one industrial country set up plants in another industrial country For example, much Japanese manufacturing in the US, and some US manufacturing in Japan, is mainly for market access.